2003
DOI: 10.1136/bmj.327.7405.18
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of hepatotoxicity associated with nimesulide and other non-steroidal anti-inflammatory drugs

Abstract: Objective To estimate the risk of acute hepatotoxicity associated with nimesulide compared with other non-steroidal anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
3
33

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(177 citation statements)
references
References 13 publications
5
136
3
33
Order By: Relevance
“…These results confirm other epidemiological studies demonstrating a small risk of severe liver injury in patients taking nimesulide and other non-steroidal antiinflammatory drugs 77 . …”
Section: Hepatic Safetysupporting
confidence: 82%
“…These results confirm other epidemiological studies demonstrating a small risk of severe liver injury in patients taking nimesulide and other non-steroidal antiinflammatory drugs 77 . …”
Section: Hepatic Safetysupporting
confidence: 82%
“…Various reports of nimesulide hepatotoxicity [11,12] have been published, though how often this condition is reported is the subject of heated debate because spontaneous reports of adverse drug events are helpful warning signals, even if they do not allow clinicians to determine incidence or relative risk. Data obtained from population-based epidemiological studies reporting the incidence or comparative risks of hospitalisation and death are, in fact, lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Traversa et al reported that, in a cohort study of thousands of patients taking various NSAIDs, ibuprofen was found to have a very low rate of liver toxicity, despite the massive use of this drug worldwide (8). Furthermore, several other studies and meta-analyses have failed to include severe liver injury as a side effect of ibuprofen use (9,10).…”
Section: Discussionmentioning
confidence: 99%